A new delay-dependent synchronisation criterion for Lur?e systems with delay feedback control. (2nd December 2011) - Xu, Jin; Zhu, Huibin; Cui, Baotong
This paper considers the H? synchronisation of a class of time-delayed chaotic systems with external disturbance. Based on delay-dividing approach, a delay-dependent synchronisation condition is obtained by constructing a new Lyapunov functional, and one simulation example is given to show the effectiveness of the proposed chaos synchronisation scheme.